MOUNTAIN AND PLAIN (Author: Don Gutteridge) and FAMILY PORTRAITS (Author: Ian Underhill) - Dorsinville, Max (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1979)
Don Gutteridge. MOUNTAIN AND PLAIN. Ian Underhill. FAMILY PORTRAITS. Toronto: McClelland and Stewart, 1978. Each: 95pp. 3.75.